2016
DOI: 10.1177/2153368716651476
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, Risky Lifestyles, and Violent Victimization

Abstract: Empirical studies have established that Blacks and Hispanics are two of the most violently victimized racial/ethnic groups in the United States, but the mechanisms that underlie these disparities in victimization risk are not well understood. This study tests a mediation model developed from criminal opportunity theories that may explain the disparities. Using data from the Project on Human Development in Chicago Neighborhoods, the results show that Black and Hispanic adolescents were twice as likely as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…With respect to youth ETV-C, the literature has emphasized the importance of deviant peers and engaging in unstructured socializing as these interactions increase opportunities for direct victimization and witnessing of violence (Antunes & Ahlin, 2015). Our findings support the idea that friends matter (see Zimmerman, Messner, & Rees, 2014), particularly for immigrant youth from different generations (Jiang & Peguero, 2017), and further suggest that opportunity for ETV-C through peer relationships may depend on race and ethnicity (Madero-Hernandez & Fisher, 2017). Distinctions in levels of unstructured socializing and deviant friendships show that youth are more susceptible to the damaging consequences of both, possibly not only because increased contact with deviant others precipitates instances of delinquency but also because the capacity to self-protect is hindered.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With respect to youth ETV-C, the literature has emphasized the importance of deviant peers and engaging in unstructured socializing as these interactions increase opportunities for direct victimization and witnessing of violence (Antunes & Ahlin, 2015). Our findings support the idea that friends matter (see Zimmerman, Messner, & Rees, 2014), particularly for immigrant youth from different generations (Jiang & Peguero, 2017), and further suggest that opportunity for ETV-C through peer relationships may depend on race and ethnicity (Madero-Hernandez & Fisher, 2017). Distinctions in levels of unstructured socializing and deviant friendships show that youth are more susceptible to the damaging consequences of both, possibly not only because increased contact with deviant others precipitates instances of delinquency but also because the capacity to self-protect is hindered.…”
Section: Discussionsupporting
confidence: 85%
“…Restricting unsupervised access to the neighborhood, limiting unstructured socializing with peers, and curbing interactions with deviant peers can reduce youth’s experience with neighborhood violence (Ahlin & Antunes, 2017; Antunes & Ahlin, 2015; Moed, Gershoff, & Bringewatt, 2017). But, although the harmful effects of peer influences may be experienced more deeply by minority youth (see Madero-Hernandez & Fisher, 2017), the deleterious impact of delinquent peers on youth deviance tends to be consistent across immigrant generational status (Jiang & Peguero, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to Hidenlang, Garofalo, and Gottfredson's theory it is revealed that a person has a great chance of being victimized because of his displayed lifestyle. The theory is quite relevant considering that people with a lifestyle that likes to expose anything in their daily lives tend to have a greater risk of danger (Madero-Hernandez & Fisher, 2017).…”
Section: Postmodern Victimology Review Of Doxing Of Vtubersmentioning
confidence: 99%
“…a sweet invitation that finally someone has a curiosity to take part in these online gambling activities. 6 But actually, this online gambling does not arise from an invitation from a bookie but also from how the surrounding environment makes someone interested in trying online gambling. This In addition to a bookie, a person who plays online slot gambling can also be sentenced to a crime in And also Lex dura, sed tamen scripta where the law is cruel, but that's how it's written.…”
Section: Victimology Review Of Online Gambling Perpetratorsmentioning
confidence: 99%